PERANCANGAN LABORATORIUM CAMPURAN HOT ROLLED SHEET (HRS â BASE) DENGAN MENGGUNAKAN ASPAL BNA BLEND 75/25 DAN ZEOLIT ALAM SEBAGAI FILLER - , Ardilson Pembuain ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The main ingredient of pavement are aggregate, fine, filler and bitumen. The use of stone dust filler at this point relatively expensive in the production process, so the alternative filler is needed. Therefore in this study the authors used natural zeolite as a filler. The asphalt as binder material in Indonesia using Pertamina asphalt although there are many various types of asphalt. One type of asphalt Buton used today is Buton Natural Asphalt Blend is 75:25, due to reasons other than its use Related research Blend 75:25 BNA still rare, this study aims to determine the characteristic Marshall and Indirect Tensile Strength in a mixture of Hot Rolled Sheet Base (HRS base) with the variations of the natural zeolite filler with dust and stone dust. This study was limited to laboratory research by referring to the specifications of the Department of Public Works 2010 revision 2, British Standard, AASHTO and ASTM. Tests were performed: (1) Marshall test, (2) test the stability of residual index, and (3) Testing of Indirect tensile strength (ITS). In this study the filler in the mixture was varied to 5 variations of zeolite, variation 1 with 0% zeolit content, variation 2 with a 25% zeolite content, variation 3 with 50% zeolite content, variation 4 with 75% zeolit content and variation 5 with zeolite content100% zeolite content. Based on the research results of Marshall test (stability value) on each variation zeolite 0%, 25%, 50%, 75%, 100% respectively are 1844.8 kg